Analisis Penyimpanan dan Pengeluaran Bahan Curah PT. Semen Padang - Suci Rahmawati SY (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2011)
Inventory are assets of a company. If the inventory control of a company is not good then the company will incur a loss, if a company's inventory control both the Performance Management will benefit. Inventory control is one of them can be done by looking at inventory turnover (ITO). Since inventory is a very important thing to do design a model that can be used as an alternative to using the approach Economic Production Quantity (EPQ). Inventory control can be done in a way determine the number of requests a year to do the calculations for the current conditions in the ITO. then performed 12 period ahead forecasting using linear, quadratic, exponential, cyclical, and cyclical trends, the Standard Error of Estimate (SEE) the smallest of each method obtained the number of requests made after that period 12 calculations Economic Production Quantity (EPQ ) to get the optimum amount of inventory as well as ITO calculations performed for the optimum amount of inventory.Based on calculations obtained ITO current state of the low of 0.010, while the ITO using EPQ is 0.230. Concluded that the inventory control for coal by using the method of generating EPQ inventory turnover is better than the methods currently used by the company.